Analisis Pendapatan dan Kesejahteraan Pedagang Pasar Kuliner Pratista Harsa Purwokerto Timur Kabupaten Banyumas - Elvina Musyarof; Sodik Dwi Purnomo; Damar Jati (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The aim of this research is to determine and analyze the significance of the influence of capital, length of business, type of outlet, working hours, rental costs and labor on the income and welfare of market traders. Pratistha Harsa Culinary, East Purwokerto, Banyumas Regency. The method used in this research is descriptive with a quantitative approach. The sample in this research is the Pratistha Harsa Culinary Market traders in East Purwokerto, Banyumas Regency as the population, with a sampling technique, namely a saturated sample, the sampling technique is by determining the entire population as a sample, namely 86 traders. The results of this research show that capital, length of business, working hours, and labor have a significant positive effect on the income of traders at the Pratistha Harsa Culinary Market, East Purwokerto, Banyumas Regency, while the type of outlet and rental costs have no effect on the income of traders at the Pratistha Harsa Culinary Market, East Purwokerto, Banyumas Regency. The implication of this research is that with the increasing length of business, traders need to increase innovation and promotion so that they can attract consumers. With the increasing number of consumers, the capital will be higher and the income earned will increase. By utilizing affordable rental costs and various types of outlets, traders are expected to be able to take advantage of Facilities as promotional materials and innovation can increase consumer demand and good use of working hours such as opening earlier at lunch time can also increase consumer demand. The more consumer demand, the greater the absorption of labor.